O tym, na co „formuł stylu nie ma”. Norwid i doświadczenie świętości - Skalińska, Ewangelina (Colloquia Litteraria, 2013)
On these for which ‘the style formula isn’t there’ [‘formuł stylu nie ma’]. Norwid and the experience of sainthood The article is an attempt to decipher certain spiritual motifs in Cyprian Norwid’s writings. The attempt is based on Rudolf Otto’s religious studies considerations, and the analysis concerns fragments of the following pieces by the Polish poet: Jasność i ciemność, Czarne kwiaty, Białe kwiaty and the poem Krzyż i dziecko.